Atrial fibrillation, antithrombotic treatment, and cognitive aging: A population-based study. (6th November 2018) - Ding, Mozhu; Fratiglioni, Laura; Johnell, Kristina; Santoni, Giola; Fastbom, Johan; Ljungman, Petter; Marengoni, Alessandra; Qiu, Chengxuan
Abstract : Objective: To examine the association of atrial fibrillation (AF) with cognitive decline and dementia in old age, and to explore the cognitive benefit of antithrombotic treatment in patients with AF. Methods: This population-based cohort study included 2, 685 dementia-free participants from the Swedish National Study on Aging and Care in Kungsholmen, who were regularly examined from 2001–2004 to 2010–2013. AF was ascertained from clinical examination, ECG, and patient registry. Global cognitive function was assessed using the Mini-Mental State Examination. We followed the DSM-IV criteria for the diagnosis of dementia, the NINDS-AIREN (National Institute of Neurological Disorders and Stroke and Association Internationale pour la Recherché et l'Enseignement en Neurosciences) criteria for vascular dementia, and the NINCDS-ADRDA (National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association) criteria for Alzheimer disease. Data were analyzed using multiple linear mixed-effects and Cox regression models. Results: We identified 243 participants (9.1%) with AF at baseline. During the 9-year follow-up period, 279 participants (11.4%) developed AF and 399 (14.9%) developed dementia. As a time-varying variable, AF was significantly associated with a faster annual Mini-Mental State Examination decline (β coefficient = −0.24, 95% confidence interval [CI]: −0.31 to −0.16) and an increased hazard ratio (HR) of all-cause dementia (HR = 1.40, 95% CI: 1.11–1.77) and vascular and mixed dementia (HR = 1.88, 95% CI: 1.09–3.23), but not Alzheimer disease (HR = 1.33, 95% CI: 0.92–1.94). Among people with either prevalent or incident AF, use of anticoagulant drugs, but not antiplatelet treatment, was associated with a 60% decreased risk of dementia (HR = 0.40, 95% CI: 0.18–0.92). Conclusion: AF is associated with a faster global cognitive decline and an increased risk of dementia in older people. Use of anticoagulant drugs may reduce dementia risk in patients with AF.